Shoulder kinetics during start-up and propulsion with a manual wheelchair within the initial phase of uninstructed training. (2nd January 2018) - Hybois, Samuel; Siegel, Alice; Bascou, Joseph; Eydieux, Nicolas; Vaslin, Philippe; Pillet, Hélène; Fodé, Pascale; Sauret, Christophe
Abstract: Purpose: Wheelchair locomotion is constraining for the upper limbs and involves a set of motor tasks that need to be learnt by a novice user. To understand this integration process, we investigated the evolution of shoulder kinetics during start-up and propulsion within the initial phase of low-intensity uninstructed training. Materials and methods: Seventeen novice able-bodied subjects performed a 120-min uninstructed practice distributed over 4 weeks. During the initial and final sessions, upper limbs kinematics and hand-rim kinetics were continuously collected. Inverse kinematics and dynamics coupled to a three-dimensional linked-segment model were used to compute shoulder net moments. Results: Participants increased the speed of the wheelchair with practice. In average, an increase of shoulder net moments and mechanical work during the push phase was observed. Conversely, during the recovery phase, participants slightly increased shoulder power but maintained a similar level of shoulder loading. However, individual evolutions allowed the definition of two groups defined as: "increasers", who increased shoulder loading and mechanical work versus "decreasers", who managed to limit shoulder loading while improving the wheelchair speed. Conclusion: These findings underline that individual adaptation strategies are essential to take into account when designing a rehabilitation protocol for wheelchair users. Implications for Rehabilitation: The learning process of manual wheelchair locomotion is essential for the assimilation of motor tasks leading individuals to select their propulsion technique. Novice users display different learning strategies: some people increase shoulder loading very early but others spontaneously manage to increase the wheelchair speed while maintaining a constant level of shoulder loading. Wheelchair rehabilitation programs should be individualized to take into account the subject-specific learning strategy.